1996
DOI: 10.1007/s004670050216
|View full text |Cite
|
Sign up to set email alerts
|

Steroid-resistant nephrotic focal segmental glomerulosclerosis: a treatable disease

Abstract: If not aggressively treated, oral steroid-resistant (SRst) nephrotic focal segmental glomerulosclerosis (FSGS) is likely to progress to end-stage renal failure. Three observations challenge the conclusion of the International Study of Kidney Diseases in Children (ISKDC) that SRst FSGS is unresponsive to further immunosuppression: (1) The ISKDC definitions of response and relapse, which fit the patterns in minimal change disease, precluded appropriate recognition of partial or gradual responses. (2) In two ISKD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(39 citation statements)
references
References 38 publications
0
38
1
Order By: Relevance
“…Tune et al showed beneficial results in 65% patients treated with multiple i.v. pulses of methylprednisolone, cyclophosphamide orally for 8-12 weeks, and tapering doses of prednisone over 30 months [5,6]. In view of significant steroid toxicity and need for several admissions for the infusions, many centers have used shorter protocols with comparable benefit, ranging between 30%and70% [3,15].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tune et al showed beneficial results in 65% patients treated with multiple i.v. pulses of methylprednisolone, cyclophosphamide orally for 8-12 weeks, and tapering doses of prednisone over 30 months [5,6]. In view of significant steroid toxicity and need for several admissions for the infusions, many centers have used shorter protocols with comparable benefit, ranging between 30%and70% [3,15].…”
Section: Discussionmentioning
confidence: 99%
“…Tune et al proposed the intravenous (i.v.) use of high doses of corticosteroids combined with oral administration of cyclophosphamide with satisfactory results [5,6]. This regimen requires multiple hospital admissions and monitoring for corticosteroid side effects.…”
Section: Introductionmentioning
confidence: 99%
“…CPH therapy and found no significant difference [17]. Steroid resistance in SRNS may be relative and, in some children, can be overcome with high-dose methylprednisolone (MPR) usually in combination with CPH or CSA [18][19][20][21]. Azathioprin and chlorambucil seem to be without therapeutic effect [12].…”
Section: Introductionmentioning
confidence: 99%
“…Five steroid-resistant patients were treated with cyclophosphamide pulse therapy and methylprednisolone, associated with prednisone, according to the protocol of Tune and Mendonza. 9 The patients were divided into 2 groups according to their initial response to the steroid therapy: Group I (steroid-responsiveresolution of the proteinuria during the first 4 weeks of continuous daily treatment with prednisone) and Group II (steroid-resistant-no response to the continuous daily treatment with prednisone for 6 weeks). Group I was further divided into 4 subgroups: IA (single episode-without recurrences), IB (infrequent relapsers-less than 2 recurrences in the 6 months after the initial response), IC (frequent relapsers-2 or more recurrences in the 6 months after the initial response), and ID (steroiddependent-recurrence during the gradual withdrawal of prednisone or 15 days after its suspension).…”
Section: Methodsmentioning
confidence: 99%